2022
DOI: 10.1021/acssuschemeng.2c02513
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Fabrication of Hollow Nano Sword-Like CuCo2O4 Derived from Bimetal–Organic Frameworks as Binder-Free Electrodes

Abstract: This study successfully synthesized highly porous hollow nano sword-like CuCo2O4 with a large specific surface area (80.2 m2 g–1) on a nickel foam substrate through a simple solution-based method followed by a calcination process. Benefiting from their geometrical merits, including excellent structural robustness, large electroactive surface areas, and 3D open structures, the hollow nano sword arrays of CuCo2O4 deliver remarkable electrochemical performances for SCs. Using this binder-free strategy, the synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 66 publications
(100 reference statements)
0
6
0
Order By: Relevance
“…Additionally, the CCOHS was shown to have a superior capacity compared to numerous previously reported findings regarding CuCo 2 O 4 -based electrode materials (mostly @1 A g –1 ), for instance, CuCo 2 O 4 microspheres (109.4 C g –1 ), CuCo 2 O 4 nanoparticles (229.5 C g –1 @2 A g –1 ), bundle-like CuCo 2 O 4 (303.22 C g –1 ), honeysuckle-like CuCo 2 O 4 /CuO composites (350.69 C g –1 ), flower-like CuCo 2 O 4 (466.4 C g –1 ), chestnut-like CuCo 2 O 4 /NF (502.4 C g –1 ), CuCo 2 S 4 /CuCo 2 O 4 nanoflowers (599.9 C g –1 ), CuCo 2 O 4 @MnMoO 4 core–shell nanosheets (663.8 C g –1 ), and CuCo 2 O 4 /MnCo 2 O 4 //graphene/Ni foam (860.4 C g –1 ) . Also, the CCOHS showed high specific capacity compared with the background of various hollow structured battery-type electrode materials summarized in Table S2 such as hollow nanosword-like CuCo 2 O 4 /NF (717 C g –1 ), NiS hollow microspheres (983.16 C g –1 ), Ni x Co 3– x O 4 hollow particles (597.96 C g –1 ), and NiCo 2 Se 4 (943.2 C g –1 ) . The CCOHS electrode also demonstrated 92% initial capacity retention with a current density increase of 10 times and 82% initial capacity retention with a current density increase of 20 times.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…Additionally, the CCOHS was shown to have a superior capacity compared to numerous previously reported findings regarding CuCo 2 O 4 -based electrode materials (mostly @1 A g –1 ), for instance, CuCo 2 O 4 microspheres (109.4 C g –1 ), CuCo 2 O 4 nanoparticles (229.5 C g –1 @2 A g –1 ), bundle-like CuCo 2 O 4 (303.22 C g –1 ), honeysuckle-like CuCo 2 O 4 /CuO composites (350.69 C g –1 ), flower-like CuCo 2 O 4 (466.4 C g –1 ), chestnut-like CuCo 2 O 4 /NF (502.4 C g –1 ), CuCo 2 S 4 /CuCo 2 O 4 nanoflowers (599.9 C g –1 ), CuCo 2 O 4 @MnMoO 4 core–shell nanosheets (663.8 C g –1 ), and CuCo 2 O 4 /MnCo 2 O 4 //graphene/Ni foam (860.4 C g –1 ) . Also, the CCOHS showed high specific capacity compared with the background of various hollow structured battery-type electrode materials summarized in Table S2 such as hollow nanosword-like CuCo 2 O 4 /NF (717 C g –1 ), NiS hollow microspheres (983.16 C g –1 ), Ni x Co 3– x O 4 hollow particles (597.96 C g –1 ), and NiCo 2 Se 4 (943.2 C g –1 ) . The CCOHS electrode also demonstrated 92% initial capacity retention with a current density increase of 10 times and 82% initial capacity retention with a current density increase of 20 times.…”
Section: Resultsmentioning
confidence: 63%
“…26 Additionally, the CCOHS was shown to have a superior capacity compared to numerous previously reported findings regarding CuCo 2 O 4 -based electrode materials (mostly @1 A g −1 ), for instance, CuCo . 22 Also, the CCOHS showed high specific capacity compared with the background of various hollow structured battery-type electrode materials summarized in Table S2 such as hollow nanosword-like CuCo 2 O 4 /NF (717 C g −1 ), 19 NiS hollow microspheres (983.16 C g −1 ), 53 Ni x Co 3−x O 4 hollow particles (597.96 C g −1 ), 54 and NiCo 2 Se 4 (943.2 C g −1 ). 55 The CCOHS electrode also demonstrated 92% initial capacity retention with a current density increase of 10 times and 82% initial capacity retention with a current density increase of 20 times.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such unusual high-rate performance is more obvious by plotting the current response at 0.3 V (vs Ag/AgCl) with the scan rate (Figure S4), where the current response increases nearly linearly with the scan rates of up to 1.0 V s –1 . According to the formula i = av b , , the b value of 0.96 and 0.95 has been obtained for the charging and discharging processes, respectively, by fitting the plots of log ( i ) vs log ( v ) over a wide scan rate range of 10–1000 mV s –1 (Figure c). It should be mentioned that the b values for the PEDOT-6h film nearly approach 1, indicative of the purely capacitive electrochemical behavior for carbon electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…Direct pyrolysis of selected MOFs to obtain metal oxide arrays has been widely reported. [112,[137][138][139][140] For example, Zheng et al reported a facile and scalable route for the in situ fabrication of ultrafine MnO nanocrystals embedded in porous carbon matrix (MnO@C), which was used as anodes for lithium-ion batteries, exhibiting a high reversible specific capacity of 1221 mAh g −1 after 100 cycles at a current density of 100 mA g −1 . [114] Tan et al also prepared a Mn-MOF derived Mn 3 O 4 with bulk oxygen defects (O d -Mn 3 O 4 @C) through valence engineering, which was used as a cathode material for aqueous Zn ion battery with ultralong cycle life.…”
Section: Self-templated Metal Oxide Arraysmentioning
confidence: 99%